Development Model of E-Budgeting and E-Reporting System on the Management of Village Fund Finance - Setyawan, Supanji; Priyono, Nuwun; Iswanaji, Chaidir (Jurnal Dinamika Akuntansi, 2017)
This study aims to analyze the ability of villages in conducting village funds management and subsequently develop e-budgeting and e-reporting system for the realization efficiency of the village fund allocation in Balesari Village. Research method used was research and development research model in which the research was conducted to develop a system. The research method used was qualitative method with case study model. The research informant was village apparatus with 10 officers. Research data was obtained by depth interview method with interviewees and field observation. The result of the research showed that the compilation of e-budgeting in budget activities of Magelang Regency Government has helped to efficient village fund realization that was by making the budget activities process, starting from planning, budgeting, to budget control became faster and could reduce the cost spent by Balesari Village Government in achieving budget realization. All of the data from the proposal stage until the end of the budget year has been integrated and stored properly so that if it is necessary the search for the origin of the budget and implementation can be quickly obtained through e-budgeting and e-reporting system. The conclusion of this study is the model of village finance that is appropriate to use is a village financial system that has been provided by the government. However, village officials are not yet ready for the implementation of Law 6/2014 and have not fully understood the management of village funds based on Permendagri 113/2014.